2020
DOI: 10.1021/acs.joc.0c01065
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal-Free Borylation of Aryl Bromide Using a Simple Diboron Source

Abstract: In this study, we developed a simple transition-metal-free borylation reaction of aryl bromides. Bis-boronic acid (BBA), was used, and the borylation reaction was performed using a simple procedure at a mild temperature. Under mild conditions, aryl bromides were converted to arylboronic acids directly without any deprotection steps and purified by conversion to trifluoroborate salts. The functional group tolerance was considerably high. The mechanism study suggested that this borylation reaction proceeds via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…(M, see SI for detail). Additionally, control experiment performed using B 2 pin 2 and base without the presence of B BiPy did not lead to the borylated product (N, see SI for detail) [37] …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…(M, see SI for detail). Additionally, control experiment performed using B 2 pin 2 and base without the presence of B BiPy did not lead to the borylated product (N, see SI for detail) [37] …”
Section: Resultsmentioning
confidence: 94%
“…Additionally, control experiment performed using B 2 pin 2 and base without the presence of B BiPy did not lead to the borylated product (N, see SI for detail). [37] The organocatalytic reaction for the formation of biaryls through arene CÀ H arylation has been accepted to involve a single electron transfer (SET) process, generating a highly reactive aryl radical species. The generation of a radical initiator from the combination of organic ligand and base have been proposed, which subsequently injects an electron to the aryl substrate.…”
Section: Bipymentioning
confidence: 99%
“…Reported in 2009, Marder and co-workers utilized the solvent in a one-pot C–H borylation/Suzuki-Miyaura cross-coupling sequence, a transformation shown to be highly effective for both aryl and heteroaryl substrates . Borylation in protic solvents such as MeOH and EtOH has also been reported including in the 2020 report on transition metal-free borylation of aryl halides using bis-boronic acid in MeOH …”
Section: Common Reactions In Dipolar Aprotic or Ethereal Solvents Rep...mentioning
confidence: 96%
“…174 Borylation in protic solvents such as MeOH 303 and EtOH 304 has also been reported including in the 2020 report on transition metal-free borylation of aryl halides using bis-boronic acid in MeOH. 305 …”
Section: Common Reactions In Dipolar Aprotic or Ethereal Solvents Rep...mentioning
confidence: 99%
“…Overall, none of the previously mentioned diboron-based reduction methods show chemoselectivity for nitro groups over vinyl groups. Previously, our group demonstrated the borylation of aryl bromides using B 2 (OH) 4 . During the study, we found that B 2 (OH) 4 showed reducing capabilities in the presence of KO t Bu without a transition-metal catalyst at mild temperatures.…”
Section: Introductionmentioning
confidence: 96%